THE BIG DATA UTILIZATION IN IMPROVING THE MICRO, SMALL AND MEDIUM BUSINESS INNOVATION IN THE PANDEMIC TIME COVID-19 - Titin Dunggio (LP2M Universitas Bina Mandiri Gorontalo, 2021)
The present study aims to identify the use of big data by businessmen in several villages in Gorontalo Regency in an effort to increase innovation for small and medium enterprises (MSMEs) during the COVID-19 pandemic. The research method is carried out with a qualitative approach through in-depth interviews with a number of businessmen affected by the COVID-19 pandemic. The stages related to the research method are data reduction, presentation of information and drawing grounded conclusions by checking the validity of data through credibility, transferability, dependability, and confirmability which increase trust. Data transferability, dependability and certainty can be presented objectively and can be justified. The results show that businessmen in Bone Bolango Regency are trying to make optimal use of big data after the COVID-19 pandemic can increase MSME innovation through three stages, namely surviving which means trying to survive in difficult conditions then making recovery related to businesses that can be saved through restructuring by optimizing the big data infrastructure as a media for information distribution, and increasing business gradually based on sharing content and information online.